ANALISIS POLA TATA RUANG TERBUKA TEPIAN SUNGAI WINONGO DI KAMPUNG BUDAYA BANGUNREJO - Pramudito, Sidhi (Universitas Atma Jaya Yogyakarta, 2013)
Abstract: Open space is one of a supporting lives the city. Its presence has an important role for the people living surrounding it. Along with development process, the quality and quantity ofÂ open space can be degraded especially when its locatedÂ in kampong. It happens because of an uncontrollable spatial layout. Yogyakarta is a city that also has a kampong, one of them is kampong Bangunrejo which crossed by Winongo River. The character and local potentials of this riverbank kampong makes the government of Yogyakarta and Forum Komunikasi Winongo Asri (FKWA) to plan a open space revitalization. It aims to improve the image a kampong through open space that located on riverbank. The aim of this research is to get a spatial layout of open spaces in kampong Bangunrejo. This spatial layout is expected to give an idea of how the open space works. The results are expected to guide open space design recommendations, corresponds to its performance. The analysis process utilised a quantitative technique using Depthmap program. By using this method, which focused on spatial layout of open spaces, would strengthen its qualitative analysis to be more real. Public open spaces were selected to represents different typologies of open space, Bangunrejo. The result of the discussion found that in general there is a relationship between the active space used as a public open space and a performance space. Performance space is influenced by aspects of connectivity (global and local integration), visual quality (visual integration), and movement patterns of people. Moreover, in a system of kampong, diversity of open space variations also affect the performance of the space.Keyword: spatial layout, public open space, space performanceAbstrak: Ruang terbuka merupakan salah satu pendukung kehidupan dalam kawasan. Keberadaan ruang terbuka memiliki peran dan fungsi penting bagi masyarakat di sekitarnya. Seiring dengan perkembangan kota, kualitas dan kuantitas ruang terbuka dapatÂ menurun, khususnya pada kawasan kampung kota. Hal ini terjadi karena pola tata ruang yang tidak terkontrol. Di Yogyakarta juga terdapat kawasan kampung kota salah satunya kampung Bangunrejo yang dilalui oleh Sungai Winongo. Karakter kampung kota dan potensi lokal yang dimiliki kampung Bangunrejo membuat pemerintah kota Yogyakarta bersama Forum Komunikasi Winongo Asri (FKWA) melakukan revitalisasi ruang terbuka tepian sungai. Program ini bertujuan untuk meningkatkan citra sebuah kampung kota melalui ruang terbuka tepian sungai. Penelitian ini bertujuan untuk mendapatkan pola tata ruang terbuka di kampung Bangunrejo yang dapat memberi gambaran bagaimana ruang terbuka tersebut bekerja. Hasilnya diharapkan dapat menjadi arahan rekomendasi desain ruang terbuka yang sesuai. Proses analisis dibantu dengan teknik kuantitatif menggunakan program Depthmap. Dengan metode deskriptif kuantitatif yang memfokuskan pada pola tata ruang terbuka akan memperkuat analisis kualitatif secara lebih nyata. Dalam proses analisis dipilih beberapa ruang terbuka publik yang dapat mewakili tipologi yang berbeda pada lokus terpilih di kampung Bangunrejo. Hasil pembahasan, secara umum menjelaskan bahwa ada hubungan antara ruang yang aktif dimanfaatkan sebagai ruang terbuka publik dengan kinerja ruang. Kinerja ruang tersebut dipengaruhi oleh aspek konektivitas (integrasiglobal danlokal), kualitas visual (integrasi visual), dan pola pergerakan. Selain itu, dalam sebuah sistem ruang kampung variasi keragaman bentuk ruang terbuka mempengaruhi kinerja ruang tersebut.Kata kunci: pola tata ruang, ruang terbuka publik, kinerja ruang